Kampar Galesong’s Donuts; Historical Development Top 5 South-Sulawesi Culinary Destination from Takalar Regency - yusuf, Hardyansyah; Muhammad Kamal Zubair; St Aminah; Mahsyar; Andi Bahri Soi (Universitas Muhammadiyah Palu, 2024)
This study aims to analyse the historical development of Kampar Galesong Donut as one of five top culinary destination in South Sulawesi Province. A qualitative description with a historical approach was used in this research method. The respondents to this research is Kampar Galesong Donut’s owners. In depth interview is required in this research inorder to get valid data. Result of this research are Kampar Galesong Donuts business began in 2017 and went viral on social media by the end of 2019. Kampar Galesong Donuts are among the top five culinary tourism destinations in South Sulawesi Province and can become a popular Takalar snack. There are several obstacles to be conquered, which peaked during the COVID-19 pandemic, when the Kampar Galesong Donuts business saw an 80% decrease in turnover as a result of the government's social distancing regulations. Donut Kampar Galesong currently has four branches and one shop dedicated to sponge cakes under the brand